Synthesis of 3-(2-hydroxy–3,4-benzophenyl-5-methoxy)-5-(4-methoxy-phenyl)–1-substituted Pyrazolines - Bijwe, A R; Bhandarkar, S E; Gholse, S B (Recent Research in Science and Technology, 2012)
1-(2-hydroxy-3,4-benzophenyl-5-methoxy)-3aryl-prop-2-ene-1-one & semicarbazide / thiosemicarbazide / phenylhydrazine /isonicotinic acid hydrazide were added to DMF and the mixture was refluxed for about 2 hours . The reaction mixture was cooled and diluted with water. The semisolid so obtained was triturated with ethanol to get a solid which was recrystallised from ethanol–acetic acid mixture to obtain titled pyrazolines